Pioneer Society of National Music: Sound and Wire Union(1940-1972) - Özdemir, Nurettin (Hakan YILMAZ, 2022)
Turkey, which has made great revolutions in every field after the proclamation of the Republic, has also entered a concise music revolution in recent years. In shaping this situation, a great responsibility fell on the artists trained in our country. While trying to create national music, the ways to be followed were created and put into practice within certain programs.One of these programs is to explain the national music to the public and popularize it.Various ways have been followed for this.The most important of these ways is to reach the public directly, that is, to give frequent concerts. For this reason, for the music revolution, it is necessary to work together stage music and the part directly reserved for the concert.It will be possible to give concerts that will transfer the well-known songs of Western music and folk songs into our language, so in this way, it will be possible to give society musical education in a new way and to spread the beautiful words of the native language. The Sound and String Association, founded in 1940 by the masters who spent their lives on the evolution of Turkish music, provided many services in line with this ideal. This purpose has been served with live concerts in the halls of the community center and concerts delivered to all corners of the country by radio broadcast. Again, conferences were given by the Sound and Wire Union Society for the evolution of national music, and publications were issued.

Cumhuriyetin ilanından sonra her sahada büyük inkılaplar başarmış olan Türkiye, son yıllarda içinde özlü bir müzik inkılabına da başlamıştır. Bu durumun şekillenmesinde ülkemizde yetişmiş sanatkârlara büyük bir vazife düşmüştür. Milli musiki oluşturulmaya çalışılırken izlenecek yollar belirli programlar dâhilinde oluşturulmuş ve uygulanmaya konulmuştur. Bu programlardan biri de oluşan batı musikisini halka anlatmak ve sevdirmektir. Yapılacak işlerden en önemlisi halka doğrudan ulaşma yani sıkça konserlerin verilmesidir. Bu nedenle musiki inkılabı için hem sahne musikisi hem de doğrudan doğruya konsere ayrılan kısmı bir arada işlemek lazımdır. Garp musikisinin tanınmış şarkıların ve halk türkülerini öz musikimize naklettirecek konserler vermek ve bu suretle halka hem yeni yolda bir musiki terbiyesi vermek hem de öz dilin güzel kelimelerini yaymak mümkün olacaktır. 1940 senesinde ömrünü Türk musikisinin gelişimi için harcayan sanatkârlar tarafından kurulan Ses ve Tel Birliği Cemiyeti oluşturulan inkılap müziği ülküsü doğrultusunda çokça hizmet vermiştir. Gerek halkevi salonlarında canlı yapılan konserler gerekse radyo yayını ile yurdun dört bir yanına ulaştırılan konserlerle bu amaca hizmet edilmiştir. Yine Ses ve Tel Birliği Cemiyeti tarafından milli musikinin gelişimi için konferanslar verilip neşriyatlar da çıkarılmıştır.
Ulusal Musikinin Öncü Cemiyeti: Ses ve Tel Birliği (1940-1972)